Design of a Rainwater Utilization System in an Urban Area: A Case Study of Graha Environesia Building, Sleman Regency - Yusuf Wiryawan; Nur Iswanto (PT Keberlanjutan Strategis Indonesia, 2026)
Water resource management in urban areas requires sustainable strategies, particularly in regions facing increasing pressure on groundwater use and rising rainwater runoff. This study aims to design a rainwater utilization system at the Graha Environesia Building, Sleman Regency, as an alternative source to partially meet clean water demand and support groundwater conservation. The study was conducted through an analysis of rainwater quality, rainfall data, building clean water demand, rainwater harvesting system calculations, pipeline network planning, water quality treatment, and estimation of system costs and environmental benefits. The Graha Environesia Building has a clean water demand of 2,750 liters per day, with a total of 90 users. The results show that most rainwater quality parameters met the required standards, except for hexavalent chromium (Cr6+), which requires treatment through an adsorption system using zeolite. The designed system is capable of collecting 5.8 m³ of rainwater per day, with a utilization efficiency of 47% of the building’s total water demand. The system requires an adsorption tank with a capacity of 0.0203 m³ using 3 kg of zeolite, with an estimated treatment efficiency of 90%. The estimated construction cost of the system is IDR 38,446,000.00. The implementation of this rainwater utilization system has the potential to reduce groundwater use by 870,000 liters per year, making it a technical and ecological solution to support groundwater conservation in urban areas.